2012
DOI: 10.1080/15548732.2012.667734
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Multiple Placements in Foster Care: A Study of Placement Instability in Five States

Abstract: In order to assess the consistency of correlates of multiple placements, secondary data from the Adoption and Foster Care Analysis and Reporting System (AFCARS) were examined for five states. The relationships between multiple placements and age, disability, and maltreatment type were consistent across the states studied. On the other hand, gender, race, and foster care system size were inconsistently related to multiple placements in terms of direction and/or strength. These results point to the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…These include poor mental health (Harden, 2004;Pasztor, Hollinger, Inkelas, & Halfon, 2006;Steen & Harlow, 2012;Tarren-Sweeney, 2008); attachment/security disorders (Harden, 2004;Tarren-Sweeney, 2008); poor physical health (Harden, 2004;Robertson, 2006); developmental disorders (Harden, 2004) and 'compromised brain functioning' (Harden, 2004). Importantly, however, not enough is known about how far poor experiences of care exacerbate conditions children may have had prior to entering care, or create new ones.…”
Section: Harmful Effects Of Impermanencementioning
confidence: 99%
See 2 more Smart Citations
“…These include poor mental health (Harden, 2004;Pasztor, Hollinger, Inkelas, & Halfon, 2006;Steen & Harlow, 2012;Tarren-Sweeney, 2008); attachment/security disorders (Harden, 2004;Tarren-Sweeney, 2008); poor physical health (Harden, 2004;Robertson, 2006); developmental disorders (Harden, 2004) and 'compromised brain functioning' (Harden, 2004). Importantly, however, not enough is known about how far poor experiences of care exacerbate conditions children may have had prior to entering care, or create new ones.…”
Section: Harmful Effects Of Impermanencementioning
confidence: 99%
“…The main risk factors included age at start of placement and, again, problematic behaviour. Similarly, a study of multiple foster care placements in five states in the US reported no overall difference between disabled and non-disabled children, except for those with behavioural disabilities, who had more moves, and 'possibly' mental health issues (Steen & Harlow, 2012).…”
Section: Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maltreatment was removal from the home because of physical abuse, sexual abuse, or neglect experienced by a child before entering the foster care system. 26 Children who were removed from the home because of a parent's prior misuse of drugs or alcohol was parental drug/alcohol exposure. 27,28 Psychosocial stressors included removal from the home because of prior parental death, parental incarceration, parental inability to cope, parental abandonment, parental relinquishment, or parental inability to provide adequate housing.…”
Section: Methodsmentioning
confidence: 99%
“…Covariates were included in the analysis that may correlate with serious health among children at end of life in foster care. Based on prior literature, 26,29,30 these covariates included gender, age, race (Caucasian or non-Caucasian), ethnicity (Hispanic or non-Hispanic), region (South, West, Midwest, and Northeast), population density (high or low), foster care support (Title IV, Medicaid, Supplemental Security Income [SSI], and other).…”
Section: Methodsmentioning
confidence: 99%